A clinical approach to parasellar lesions in the transition age. (17th June 2021) - Sbardella, Emilia; Puliani, Giulia; Feola, Tiziana; Pofi, Riccardo; Pirchio, Rosa; Sesti, Franz; Verdecchia, Federica; Gianfrilli, Daniele; Moffat, Daniel; Isidori, Andrea M.; Grossman, Ashley B.; ,
Abstract: Many reviews have summarised the pathology and management of the parasellar region in adult patients, although an analysis of these aspects in the transition years, from puberty onset to the age of peak bone mass, has been lacking. A comprehensive search of English‐language original articles, published from 2000 to 2020, was conducted in the MEDLINE database (December 2019 to March 2020). We selected all studies regarding epidemiology, diagnosis and management of the following parasellar lesions: germinoma, craniopharyngioma, Langerhans cell histiocytosis, optic glioma, hypothalamic hamartoma, tuber cinereum hamartoma, cranial chordoma, Rathke cleft cyst, hypophysitis and hypothalamitis during the transition age from childhood to adulthood. In the present review, we provide an overview of the principal parasellar lesions occurring in the transition age. Symptoms are usually a result of the mass effect of the lesions on nearby structures, as well as anterior pituitary deficits. Diabetes insipidus occurs frequently in these patients. In this age group, pubertal developmental disorders may be more evident compared to other stages of life. Parasellar lesions in the transition age mostly include neoplastic lesions such as germinomas, hamartomas, optic gliomas, craniopharyngiomas Langerhans cell histiocytosis and chordomas, and rarely inflammatory lesions (hypophysitis, hypothalamitis). There are limited data on the management of parasellar lesions in the transition age. Endocrine evaluation is crucial for identifying conditions that require hormonal treatment so that they can be treated early to improve the quality of life of the individual patient in this complex age range. The clinical approach to parasellar lesions involves a multidisciplinary effort. Abstract : This is a review on parasellar lesions in the transition age from childhood to adulthood.